Sprzątanie w wielkim mieście. Polskie imigrantki na nowojorskim rynku pracy. Część 2: Sprzątaczki w domach prywatnych jako przedsiębiorstwa usługowe z marką etniczną - Anna Sosnowska (University of Warsaw, Centre of Migration Research (CMR), 2014)
– An interpretation of domestic cleaners' work as experienced by Polish immigrants in New York City is presented in this text. It argues that the elements of this work that cleaners appreciated themselves are the characteristics of the small immigrant enterprise whose place on the market relies heavily on strong ethnic brand. These characteristics are: significant amount of autonomy; operating under the owners' own financial risk and on the basis of contract between relatively equal partners; depersonalized, standardized and professional service is delivered under conditions of trust and with significant amount of emotional labor. This immigrant business sector relies on immigrant networks and recommendation. A 'Polish maid' is an ethnic brand appreciated in New York City.
Keywords: 330; labor migrants; New York City (United States); cleaners; ethnic queue